أنظمة ومنشات توزيع المياه في الفترة القديمة القناة الرومانية بإقليم الزاب الشرقي أنموذجا - بن قربة, صالح; جمال, عناق ، (Sciences de l'Homme et de la Société; Vol. 19 (2016): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ)
أجمع المختصون على الدور الكبير الذي لعبه الرومان في مجال الإنشاءات المائية، وتخليد ماضيهم بتقاليد وتقنيات مائية رائعة في كامل المستوطنات التي ضموها إلى إمبراطوريتهم. بما فيها منطقة نوميديا والتي يرتبط بها إقليم الزاب الشرقي، ولعل من أهم مخلفاتهم ومنشاتهم المائية في هذا الإقليم، نجد القناة المائية التي تعرف بقناة ملاقو أو قناة بادس، ارتباطًا بمكان نبعها ومصبها والتي تشهد على تحد كبير أنجزه القدماء في مواجهة كل الظروف الطبيعية والمناخية وحتى الطبوغرافية التي تتميز بها المنطقة.   Abstract : Just like all the other Algerian oases in the middle of the Saharan desert, the ziban oasis owes its survival to water and its brilliant ancient irrigation system. The diverse heritage and complex yet fragile structure of the oases have affected their evolution. Constant evolution prevents crisis situations making oases quite durable. Their production system depends on irrigation: when the necessary water is available, agricultural activities flourish, the social and cultural balance improves creating a dynamic equilibrium which maintains the oasis in a state of stability. In antiquity in this region an impressive 70km long aqueduct was constructed with several phases. The aqueduct was constructed to transfer water from the rich springs of “Mountain auresse" to the capital of ''eastern zab'' The aqueduct starts from a river "malleguou" and is wisely designed to provide irrigation to the crops. On the outskirts of the region the aqueduct branched out to supply fountains and reservoirs.